AKTIVITAS FISIK AKUT INTERVAL DAN KONTINYU INTENSITAS MODERAT TIDAK DAPAT MENURUNKAN KADAR BIOMARKER RESORPSI TULANG CTx - Triardhana, Yanuar Alfan; Sari, Gadis Meinar; Liben, Paulus (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Physical activity will affect the bone remodeling process and have an impact on bone health. Physical activity would activate osteoblasts and precursor through lane HPA Axis to start the process of bone remodeling. When the process of remodeling of bone occurs there are molecules of collagen which is released into the circulation, i.e. CTx (osteoclast marker). The aim of this study to showing effect of acute continuous and interval physical activity with moderate intensity on CTx. This research was using the type of research field experimental by using the pretest-posttest design. Sixteen adult male was selected on this study and devided into 2 with 8 people every group. Blood sample was taken before and 1 hour after the physical activity. The results obtained showed the acute effect of continuous physical activity with moderate intensity to CTx with a mean pretest 0,93 ± 0,566 posttest 0,559 ± 0,398 ng/mL (p = 0.173 0.05), acute effect of moderate intensity interval physical activity on CTx with the mean pretest 0,451 ± 0,302 posttest 0,524 ± 0,284 ng/mL (p = 0.693 0.05). From this study can be concluded that there was no effect of acute continuous and interval physical activity with moderate intensity on CTx.